The Incongruity Factor: Random Answers Without Questions - Tom McCormick (Journal of Applied Communications, 1977)
A transcript of an interview Mr. McCormick had with himself. He reports that the interview, on the whole, went smoothly and conformed, in general, to accepted theories of communications.